Method and unit for dynamic control of conversion characteristics of spectrometric paths for multichannel charged particle registration systems. (December 2020) - Tuboltsev, Yu V; Bogdanov, A A; Chichagov, Yu V; Eremin, I V; Eremin, V K; Verbitskaya, E M
Abstract: A method and unit for dynamic control of conversion characteristics of spectrometric paths of multichannel charged particle registration systems based on specialized microchip with a large degree of integration similar to IDE1140 in structure is proposed. The conversion characteristics are controlled during operation of the device by auto-adjusting the offset and gain of the scaling amplifier. The proposed method allows to use the entire dynamic range of the analog-to-digital converter and adjust the temperature drift for each channel at the hardware level during operation of the device.